2002
DOI: 10.1042/bj20021083
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of c-jun mRNA in cardiac myocytes requires the extracellular signal-regulated kinase cascade, but c-Jun N-terminal kinases are required for efficient up-regulation of c-Jun protein

Abstract: Cardiac hypertrophy, an important adaptational response, is associated with up-regulation of the immediate early gene, c-jun, which encodes the c-Jun transcription factor. c-Jun may feed back to up-regulate its own transcription and, since the c-Jun N-terminal kinase (JNK) family of mitogen-activated protein kinases (MAPKs) phosphorylate c-Jun(Ser-63/73) to increase its transactivating activity, JNKs are thought to be the principal factors involved in c-jun up-regulation. Hypertrophy in primary cultures of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…HEK 293 cells lines stably overexpressing the FLAGtagged ␤ 2 AR-GFP were cultured as described (22). Preparation and short-term culture of neonatal rat ventricular myocytes were as described (23,24), where 24 h after plating they were placed in low-serum medium.…”
Section: Methodsmentioning
confidence: 99%
“…HEK 293 cells lines stably overexpressing the FLAGtagged ␤ 2 AR-GFP were cultured as described (22). Preparation and short-term culture of neonatal rat ventricular myocytes were as described (23,24), where 24 h after plating they were placed in low-serum medium.…”
Section: Methodsmentioning
confidence: 99%
“…The anthrapyrazolone SP600125 has recently been characterized by Bennett et al (2001) as a novel inhibitor of JNK catalytic activity. This compound inhibits JNK1, JNK2 and JNK3 with a high specificity (IC 50 : 0.04-0.09 mM) and several laboratories have used this inhibitor to characterize the role of JNK in several cellular processes (Clerk et al, 2002;Shin et al, 2002;Hashimoto et al, 2003;Besirli and Johnson, 2003). SP600125 has been tested on different kinases, including MAPKs ERK and p38 and the serine threonine kinase PKA (Bennett et al, 2001), and has been found to have no in vitro inhibitory effects on the activities of these kinases in the concentration we used.…”
Section: Inhibition Of Jnk Results In Decreased Invasion Of Meningocomentioning
confidence: 99%
“…Activated JNK in turn could phosphorylate transcription factors, c-Jun and ATF-2, which are components of the dimeric activating protein (AP)-1 [49][50][51] . Here, we determined the expression of phospho-JNK and JNK in VES-stimulated SGC-7901 cells.…”
Section: Discussionmentioning
confidence: 99%